Rare Disasters, Financial Development, and Sovereign Debt - REBELO, SERGIO; WANG, NENG; YANG, JINQIANG (Journal of Finance, 2022)
ABSTRACT We propose a model of sovereign debt in which countries vary in their level of financial development, defined as the extent to which they can issue debt denominated in domestic currency in international capital markets. We show that low levels of financial development generate the “debt intolerance” phenomenon that plagues emerging markets: it reduces overall debt capacity, increases credit spreads, and limits the country's ability to smooth consumption.